2021
DOI: 10.1186/s13561-021-00333-z
|View full text |Cite
|
Sign up to set email alerts
|

Which factors increase informal care hours and societal costs among caregivers of people with dementia? A systematic review of Resource Utilization in Dementia (RUD)

Abstract: Background Nearly 19 million people across OECD countries are living with dementia, and millions of family caregivers are affected by the disease. The costs of informal care are estimated to represent 40–75% of the total dementia cost exceeding formal care time and medical costs. Objective To conduct a systematic review to evaluate the methodological quality and factors associated with high informal care hours per month that increase societal costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Our results are of key importance for stakeholders and clinicians because creating smaller wards with userfriendly environments, in addition to better staffing can support family involvement and user-involvement. This article extends the traditional method of estimating formal and informal NH care based on ADL and supervision task calculations [7,15,17]. We found that 7 hours of informal direct care per month in Norwegian NHs is relatively low compared to other European countries.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our results are of key importance for stakeholders and clinicians because creating smaller wards with userfriendly environments, in addition to better staffing can support family involvement and user-involvement. This article extends the traditional method of estimating formal and informal NH care based on ADL and supervision task calculations [7,15,17]. We found that 7 hours of informal direct care per month in Norwegian NHs is relatively low compared to other European countries.…”
Section: Discussionmentioning
confidence: 71%
“…This article extends the traditional method of estimating formal and informal NH care based on ADL and supervision task calculations [ 7 , 15 , 17 ]. We found that 7 hours of informal direct care per month in Norwegian NHs is relatively low compared to other European countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations